Effect of Worklife Balance on Organizational Citizenship Behaviour in Environmental Agencies within North Rift Region, Kenya - Chepkemoi , Judith (African Journal of Education,Science and Technology (AJEST), 2021)
The study determined the effect of work life balance on OCB. Job embeddedness theory guided the study. The study employed pragmatism approach and explanatory research design. 935 employees of Environmental Agencies within North Rift region formed the target population of the study. A sample size of 274 respondents was selected using multi stage sampling technique closed ended questionnaires and structured interview schedule were used to collect primary data for the study. Descriptive and inferential statistics were used to analyze quantitative data while qualitative data was analyzed thematically. Hypothesis was tested using multiple regression model. Findings of this study indicated that work life balance improves OCB (β=.129, p= 0.00<0.05). The implication is that work life balance has the ability to enhance and impact employee behavior and attitudes for the organization. It therefore calls for formulation of work life policies which can promote employee welfare through proper time balance in their work place.